Treatment of gastric eosinophilia by epicutaneous immunotherapy in piglets sensitized to peanuts. Issue 12 (20th October 2017) - Mondoulet, L.; Kalach, N.; Dhelft, V.; Larcher, T.; Delayre‐Orthez, C.; Benhamou, P. H.; Spergel, J.; Sampson, H. A.; Dupont, C.
Summary: Background: Eosinophilic gastrointestinal disorders (EGIDs) are hypersensitivity disorders frequently triggered by food allergy and manifested by mucosal eosinophilic infiltration at any level of the gastrointestinal tract. This study established a model of gastric eosinophilia in peanut‐sensitized piglets to evaluate the efficacy of epicutaneous immunotherapy (EPIT) for its treatment. Methods: Experiments were carried out in piglets first sensitized by three intra‐peritoneal injections of peanut protein extract (PPE) with adjuvant, and then given PPE orally for 10 days, a sequence leading to gastric eosinophilia assessed by endoscopy. For 3 months, eight piglets received active EPIT, using Viaskin ® loaded with PPE, applied daily on the ear, while eight received placebo EPIT (Placebo). Piglets were exposed to a second 10‐day period of PPE orally. Lesions were scored by endoscopy on the last day of PPE exposure. After killing, all parts of the digestive tract were analysed by a pathologist unaware of the piglets' status. IgE response was measured, and mechanistic parameters were analysed in the spleen. Results: After sensitization, a significant increase of total IgE was observed in sensitized compared to naive animals (61.1 ± 13.3 vs 27.8 ± 6 ng/mL, P < .01). Following oral intake of PPE, sensitized piglets developed moderate gastritis compared to naive piglets (1.5 vs 1.0, median score). After 3 months of immunotherapy, median IgE was significantly reduced in EPIT vs placebo piglets (61.4 ± 16.3 vs 105.9 ± 25.6 ng/mL, P < .01). Active EPIT significantly reduced gastric mucosal lesions induced by PPE oral intake (macroscopic score 0 [0‐2] vs 2 [1‐3], P < .01, respectively, active vs placebo) and gastric mucosa eosinophils counts (239 eosinophils/mm 2 [59‐645] vs 2554 eosinophils/mm 2 [462‐8057], P < .01, respectively active vs placebo). GATA‐3, IL‐5 and eotaxin mRNA expression decreased significantly after EPIT ( P < .05). Conclusions: This study describes a large animal model of gastric eosinophil in peanut‐sensitized piglets. Utilizing this model, we demonstrated the efficacy of EPIT in treating peanut‐induced EGIDs.